2017
DOI: 10.5296/jab.v6i1.11811
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Mushroom Farmers in Swaziland

Abstract: Mushrooms have been cultivated in Swaziland since 2001 as part of a long-term programme which sought to improve rural livelihoods through commercial production of non-conventional high-value commodities. Despite the mushroom enterprise gaining popularity in a number of Sub-Saharan African (SSA) countries, where production is dominated by rural-based small-scale farmers, limited research has been done to study the technical efficiency of mushroom farmers in Swaziland.The primary objectives of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The labor factor has a positive impact of 0.237, which increases the production risk of sugarcane. The findings of this study are consistent with studies by Dlamini et al [15], Ali and Jan [16], and Ali et al [11] that demonstrated the beneficial impact of labor on sugarcane yield. The t-test results, however, revealed that labor had no appreciable impact on the risk associated with sugarcane output.…”
Section: Sugarcane Risk Function In Malang Regencysupporting
confidence: 93%
“…The labor factor has a positive impact of 0.237, which increases the production risk of sugarcane. The findings of this study are consistent with studies by Dlamini et al [15], Ali and Jan [16], and Ali et al [11] that demonstrated the beneficial impact of labor on sugarcane yield. The t-test results, however, revealed that labor had no appreciable impact on the risk associated with sugarcane output.…”
Section: Sugarcane Risk Function In Malang Regencysupporting
confidence: 93%